Sin, Penance And Confession From A Protestant Perspective - Nowosad, Sławomir (Studia Theologica Varsaviensia, 2020)
Although the reality of evil and moral weakness belongs to the most common human experience, only rational analysis does not allow for the rightful understanding of these aspects of the human condition. Christianity comes to man’s aid here when it sheds supernatural light on its essence and Divine origin, and at the same time on weakness and the need of grace. In view of the entire Christian tradition, Protestantism appears as an important and serious tradition, however evaluated sometimes as unilateral or extremely pessimistic. "e Reformational assumptions and multi-century subsequent history of theological thought and sacramental-pastoral practice, particularly in Lutheran, Calvinist and Anglican tradition, demand careful studies and analyses, so that this aspect of human fate and supernatural destiny should be comprehensively understood.